LIDERANÇA E ABSENTEÍSMO ENTRE TRABALHADORES DE NÍVEL OPERACIONAL - GALVÃO JÚNIOR, NIVALDO SALES (2018)
Leadership plays a key role in organizational processes and outcomes, whether at the individual, group or organizational level. The relationship between leadership and its consequences has been the focus of efforts over the last decades, however, it is still possible to identify important empirical gaps, among them its relation to absenteeism. This study aimed to investigate the correlations between leadership and absenteeism among workers at the operational level of a mixed-economy enterprise. The intention was to analyze the satisfaction of the workers in the attitude of the leadership in the transformational and transactional perspective and what is the greatest malaise factor related to absenteeism from the point of view of the respondents and especially if there is a correlation between the dimensions of leadership and the factors absenteeism at work. The research sample consisted of 136 operational employees of the Brazilian Post and Telegraph Company, classified as Post - Treatment agents. Workers at two post-order processing centers in the city of São Paulo. The instruments used to evaluate the variables of the study were the Attitudes Scale Facing Styles of Leadership, by 32 items and distributed in two dimensions: transformational leadership and transactional leadership and the Work Absenteeism Scale, composed of 22 items distributed in 4 factors related problems: Interpersonal and workplace factors; Psychosomatic factors and working conditions; Administrative-labor factors; Factors of time and career management. In addition, participants should respond to a sociodemographic questionnaire. Data were analyzed using descriptive and correlational statistical techniques. The results indicated that employees have an unsatisfactory perception when the immediate manager presents transactional leadership attitudes and are indifferent when it is demonstrated aspects related to transformational leadership. The psychosomatic factor and working conditions presented the greatest reason for absence indicated by the respondents. It was found that there is a slight correlation between the two dimensions of leadership with the factor of time and career management. The more employees are satisfied with the performance of the transformational and transactional leader, the less they claim they lack the sense of career paralysis, the need for time to study, and solve unforeseen personal issues. It is concluded that the satisfaction with leadership presents a slight negative correlation with absenteeism.